2018
DOI: 10.1016/j.psychres.2018.08.055
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mood and attitudes towards eating on cognitive and autobiographical memory flexibility in female university students

Abstract: Cognitive flexibility, as measured through set-shifting ability, appears to be impaired in patients with eating disorders (EDs). Thus, it is important to determine if the switching deficit seen in clinical eating disorders generalizes to participants with a subclinical disordered eating. Another deficit manifested by clinical and subclinical disordered eating is the ability to retrieve specific autobiographical memories. It is possible that deficits in autobiographical memory retrieval extends to the ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…The Brixton Spatial Anticipation Test (Burgess & Shallice, 1996) is regarded to be a measure of frontal executive function and is widely used in Europe in clinical practice (Lezak, Howieson, Bigler, & Tranel, 2012) and research (Bagshaw, Gray, & Snowden, 2014;Bayliss & Roodenrys, 2000;Cammisuli & Sportiello, 2017;Darcy et al, 2012;Hornberger et al, 2010;Lough et al, 2006;Lounes, Khan, & Tchanturia, 2011;Mang, Ridout, & Dritschel, 2018;McGuinness, Barrett, McIlvenna, Passmore, & Shorter, 2015;Primativo et al, 2017;Reay, Hamilton, Kennedy, & Scholey, 2006;Staios et al, 2013). The test requires participants to predict the location of a coloured dot as it moves over successive pages according to nine underlying rule occurrences.…”
Section: Introductionmentioning
confidence: 99%
“…The Brixton Spatial Anticipation Test (Burgess & Shallice, 1996) is regarded to be a measure of frontal executive function and is widely used in Europe in clinical practice (Lezak, Howieson, Bigler, & Tranel, 2012) and research (Bagshaw, Gray, & Snowden, 2014;Bayliss & Roodenrys, 2000;Cammisuli & Sportiello, 2017;Darcy et al, 2012;Hornberger et al, 2010;Lough et al, 2006;Lounes, Khan, & Tchanturia, 2011;Mang, Ridout, & Dritschel, 2018;McGuinness, Barrett, McIlvenna, Passmore, & Shorter, 2015;Primativo et al, 2017;Reay, Hamilton, Kennedy, & Scholey, 2006;Staios et al, 2013). The test requires participants to predict the location of a coloured dot as it moves over successive pages according to nine underlying rule occurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research in the general population has shown that executive function problems are associated with subclinical disordered eating behaviours 13,14,24,25 and clinical eating disorders 15,26 . In particular, studies have shown that problems in the specific domains of set‐shifting and emotional control are associated with disordered eating behaviours and eating disorders 13,14,16 . Set‐shifting refers to a person's ‘ability to move freely from one situation, activity, or aspect of a problem to another, as the circumstances demand’ 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research in the general population has suggested that problems with executive function are associated with disordered eating behaviours 13,14 and clinical eating disorders 15,16 . However, there is limited research about this association in persons with type 1 diabetes, especially in the vulnerable adolescent age group 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported that the EFs of individuals with BED, seem to be weak [5,8,[29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%